Suspected inflammatory rheumatic diseases in patients presenting with skin rashes. Issue 4 (August 2019) - Alves, Francisca; Gonçalo, Margarida
Abstract: Skin lesions occur, often at very early stages, in many of the most frequent inflammatory rheumatic diseases such as in systemic lupus erythematosus (SLE), dermatomyositis (DM), systemic sclerosis (SSc), Sjögren's syndrome, rheumatoid arthritis (RA), and psoriatic arthritis. It is important to recognize the different specific cutaneous lesions in SLE (e.g., "butterfly" rash in acute, annular or psoriasiform photosensitive lesions in the subacute form, and discoid lesions in the chronic form) for an early diagnosis and to estimate the associated risks of internal disease, whereas nonspecific lesions (exanthema, vasculitis, and alopecia) can be part of SLE flares. Cutaneous lesions in DM (Gottron's papules and sign, heliotrope rash, dystrophic cuticles, and nailfold capillary abnormalities) may occur before any clinically evident muscular or systemic organ involvement and are of utmost importance for early diagnosis. The pattern of cutaneous lesions and associated autoantibodies also allow the distinction of different phenotypes, either more prone to life-threatening interstitial lung disease (MDA-5) or with higher risk for neoplasia (TIF1-γ). Many other skin lesions, although not specific, require further investigation to look for a possible underlying inflammatory rheumatic disease: non-pruritic urticarial lesions in anti -C1q-associated urticarial vasculitis, Still's disease or hereditary auto-inflammatory syndromes, transient macular purpura of vasculitis in Sjögren's syndrome, Behçet's disease, or RA, Raynaud's phenomenon in SSc and mixed connective tissue disease, erythema nodosum or other panniculitis in RA, Behçet's disease and SLE, pustular eruptions in Behçet's disease, psoriasis, and hereditary auto-inflammatory syndromes. After reviewing in detail the cutaneous manifestations of the most frequent inflammatory rheumatic diseases, we describe a topographic and morphological approach to skin rashes, calling attention to facial rashes, hand involvement, scalp, nail, or leg lesions or to some morphological aspects of skin lesions (annular, pustular, urticarial, or exanthematous) that may be the initial manifestations of inflammatory rheumatic diseases. The importance of skin lesions is confirmed by their presence as part of the classification criteria of many inflammatory rheumatic diseases. They also contribute to early diagnosis, to characterize disease phenotypes, to aid in effective patient management, and, ultimately, to impact on disease prognosis.